2018
DOI: 10.1016/j.joco.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint assessment of demarcation line depth after standard and accelerated cross-linking in central and inferior keratoconus

Abstract: PurposeTo determine the changes in the depth of the demarcation line in the central to peripheral cornea following accelerated compared to standard corneal cross-linking (CXL).MethodsIn this prospective, non-randomized study, 60 eyes with progressive keratoconus underwent accelerated or standard CXL (30 in each group). Anterior segment optical coherence tomography (AS-OCT) was done one month later by two independent masked examiners to measure the depth of the demarcation line in the central cornea and on peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The only morphological difference, however, is the depth of the demarcation line. 27,28 It is remarkable, that lower irradiances produce deeper demarcations lines showing a good correlation with the oxygen kinetics found in this study. However, it is still unknown how much CXL is required to stabilize keratoconus.…”
Section: J O U R N a L P R E -P R O O F Discussionsupporting
confidence: 85%
“…The only morphological difference, however, is the depth of the demarcation line. 27,28 It is remarkable, that lower irradiances produce deeper demarcations lines showing a good correlation with the oxygen kinetics found in this study. However, it is still unknown how much CXL is required to stabilize keratoconus.…”
Section: J O U R N a L P R E -P R O O F Discussionsupporting
confidence: 85%
“…Recent studies by Mathews et al 83 , correlating the corneal densitometry after CXL to visual acuity, demonstrated that, although the greatest and most durable post-CXL densitometry change was in the anterior layer, the degree of increased densitometry haze in the mid-stromal layer was mostly associated with (possibly predictive factor) improvement in CDVA, maximum K, and HOAs. The persistence of corneal haze at 6 months, measured by increased densitometry, might be a prognostic marker for CXL effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether accelerated CXL procedures warrant a sufficient crosslinks amount, distribution and saturation to maintain long-term stability similar to Epi-Off S-CXL remains an open question. Asgari et al 83 reported a lot of values for the depth of DL for several irradiances, see Table 1. From these DL depths the relative DL was calculated as…”
Section: Figure 6 Demarcation Line After Mazzotta's Enhanced Fluencementioning
confidence: 99%
“…The need to compare the results obtained with the different protocols has required the setting of parameters apt to predict if the treatment is successful or not, as the changes in best-corrected visual acuity and K readings [ 20 ] or the changes in corneal density [ 21 ]. A parameter that today seems to satisfy the need of indirect predictor of effectiveness is the demarcation line [ 9 ], and various studies compare the effectiveness of different cross-linking protocols based on the demarcation line [ 11 , 12 , 13 , 22 ]. Several authors believe that its identification and the depth that the line reaches at the stroma level are a predictor of the effectiveness of the treatment because, indeed, the stroma seems to be more resistant after the treatment [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demarcation line appears on the AS-OCT imaging as a hyper-reflective line in the corneal stroma, at a variable depth [ 11 ]. Its presence, and the depth that the line reaches at the stromal level, might be considered as an indirect predictor of the effectiveness of the treatment as it represents the transition between the anterior treated stroma and the posterior untreated stroma; various studies are comparing the effectiveness of different CXL protocols based on this indirect parameter [ 11 , 12 , 13 ]; nevertheless, Yam et al failed to find a correlation between demarcation line depth and change in visual acuity and in steepest K at 6 months [ 14 ]. The aim of the study is to visualize and evaluate the characteristics of the demarcation line one month after a novel CXL protocol named epithelium-off iontophoresis CXL (epi-off I-CXL) as assessed by AS-OCT.…”
Section: Introductionmentioning
confidence: 99%